Archetyp radykalizmu rosyjskiego: Protopop Awwakum i car Aleksiej Michajłowicz - Kisielowa, Marina (Przegląd Rusycystyczny, 2006)
ARCHETYP RADYKALIZMU ROSYJSKIEGO: PROTOPOP AWWAKUM I CAR ALEKSIEJ MICHAJŁOWICZ Streszczenie Ruch protopopa Awwakuma to objaw kryzysu kultury Rusi Moskiewskiej XVII wieku. Paradoksem starego obrządku jest fakt, że kwestionując reformę cerkiewną, broniąc „litery” słowa, podważa jej „ducha”, tworząc precedens „wolnego słowa” kultury rosyjskiej, opozycyjnego wobec systemu politycznego. ARCHETYPE OF RUSSIAN RADICALISM: PROTOPOP AVVAKUM AND THE TSAR ALEKSEI MIKHAILOVICH Summary Protopop Avvakum’s movement is a symptom of cultural crisis of Muscovite Rus of the 17th century. The paradox of the Old Belief is the fact that while defending the ‘letter’ of the word and disputing the Russian Church Reform, it is questioning its ‘spirit,’ forming a precedent of the ‘free word’ (being in opposition against the political system) of Russian culture.